Design and development an active mass damper for broadband vibration control - Ladipo, Ismail; Abdul Muthalif, Asan Gani; Rozaime, Alif; Asyraf, Ahmad (2011)
Civil structures experience vibrations due to natural dynamic forces such as earthquakes and wind loads. Often, mass-spring system is used to reduce such vibrations. The mass-spring system can either serve as absorbers or dampers. Usually, such system is tuned to absorb or damp a single frequency of excitation or resonance frequency respectively. However, ability to vary the absorber’s natural frequency would allow broadband vibration absorption. In this paper, an Active Mass Damper (AMD) is presented to eliminate broadband vibration. The lowest frequencies are the main interest as they cause larger displacement. The AMD is tuned actively to match the first three resonance frequencies of a three story building model thus making it effective for a broadband vibration control. The tuning of AMD’s natural frequency is done using piezoelectric patch that effectively change its stiffness. Simulation studies on the performances of the AMD are shown. The optimal location of the AMD is also identified. The findings of this study shows reduction in all response of the individual floors at the resonance frequencies.